2016
DOI: 10.5539/gjhs.v8n10p143
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Oral Health Attitudes and Behavior of Dental and Medical students, Yemen

Abstract: Yemeni dental and medical students have shown markedly poor oral health attitude and behavior. Further studies are required to reveal possible shortcoming in these schools' education process. Dental and medical curricula should emphasize the importance of proper oral hygiene, and further participation of medical and dental students in oral hygiene seminars is highly encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
38
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 0 publications
9
38
1
4
Order By: Relevance
“…Recently, several studies evaluated this educational transition in different regions of the world comparing the oral health attitudes and behaviour among preclinical and clinical dental students as primary signs for educational progress. Several outcomes displayed significant improvements of oral health manners in clinical students [4,[10][11][12][13][14][15][16][17], whereas others observed a less effective preclinical-clinical transition [18,19]. Examining the literature, no similar investigation was found in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies evaluated this educational transition in different regions of the world comparing the oral health attitudes and behaviour among preclinical and clinical dental students as primary signs for educational progress. Several outcomes displayed significant improvements of oral health manners in clinical students [4,[10][11][12][13][14][15][16][17], whereas others observed a less effective preclinical-clinical transition [18,19]. Examining the literature, no similar investigation was found in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies were conducted at different faculties and in different environments and they all showed the same, that constant professional development of students reflects on their oral hygiene 37,38 . To serve as a good model, the improvement of oral health-related behavior and attitude should be started from the 1st year of education 39 .…”
Section: Discussionmentioning
confidence: 99%
“…A study in Yemen on 1 st to 5 th year medical and dental students using the same questionnaire reported similar findings to ours. 13 A study in Spain also reported more favourable dental health habits among third-year students compared to medical students in the same grade 25 . It seems that dental education experience of dental students even in non-clinical stage potentially improves their oral health attitudes and behaviours 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Oral health attitudes and behaviour among medical and dental students in Tehran, Iran HU-DBI questionnaire has been administered in many countries such as UK, 9 USA, 10 South Korea, 11 China, 12 Yemen, 13 Greece, 14 Romania, 15 Turkey, 16 India 17,18 and Jordan. 19 Thus, it can provide the possibility of comparison among various countries, and to assess cross-cultural differences.…”
Section: Introductionmentioning
confidence: 99%